Effect of Pumpkin Husks on Cracker Dough Fermentation - Zaitseva I.; Shelamova S.; Derkanosova N. (Техника и технология пищевых производств)
An acute deficiency of food fibers is one of the most urgent problems of balanced diet. Food status can be increased by fortifying food formulae with natural raw ingredients that are rich in alimentary fibers. Dry residue of fruit and vegetable husks is a by-product of mother juice. Pumpkin husks were selected as an ingredient for cracker dough as a result of preliminary comparative researches of its structure and functional and technological properties. Pumpkin husks are a powdery product of cream color with an orange shade, humidity = 5.3%, cellulose = 19.6%, hemicelluloses = 3.5%, pectin = 5.4%. The research objective was to establish the effect of pumpkin husks on the dough fermentation process, since fermentation is one of the major factors that define the quality of the finished product. Methods of mathematical planning were used to calculate the optimal dose of pumpkin husks as 83.53 kg per ton of finished product. A set of experiments defined the biotechnological processes during dough maturation. Pumpkin husks proved to promote acid accumulation; they also increased the quantity of yeast cells and budding yeast cells. The effect can be due to the high content of digestible yeast cells of sugars. In addition, pumpkin husks are rich in magnesium, phosphorus, zinc, and other substances that produce a favorable impact on yeast microflora. The experimental dough sample demonstrated a better dimensional stability, which is connected with redistribution of moisture due to the water absorbing properties of food fibers and the reducing sugars in pumpkin husks. The cracker dough with pumpkin husks had a better plasticity, which helped to form the layered structure of the finished products. The effect can be explained by the more intensive process of acid accumulation. The results of the biotechnological fermentation processes of the cracker dough with pumpkin husks were confirmed by test baking. The paper features a comparative analysis of the crackers with pumpkin husks and the control sample. Introduction of pumpkin husks into the cracker formulation proved to have a favorable effect on the activity of yeast microflora, which improved the biotechnological processes and partially leveled the strengthening effect of food fibers of pumpkin husks on the cracker dough. As a result, the quality of the finished products met the standard requirements.